Bioinformatics analyses and biological function of lncRNA ZFPM2-AS1 and ZFPM2 gene in hepatocellular carcinoma - Luo, Yi (Oncol Lett, 2020)
Hepatocellular carcinoma (HCC) remains one of the most lethal malignant tumors worldwide; however, the etiology of HCC still remains poorly understood. In the present study, cancer-omics databases, including The Cancer Genome Atlas, GTEx and Gene Expression Omnibus, were systematically analyzed in order to investigate the role of the long non-coding RNA (lncRNA) zinc finger protein, FOG family member 2-antisense 1 (ZFPM2-AS1) and the zinc finger protein, FOG family member 2 (ZFPM2) gene in the occurrence and progression of HCC. It was identified that the expression levels of lncRNA ZFPM2-AS1 were significantly increased in HCC tissues, whereas expression levels of the ZFPM2 gene were significantly decreased in HCC tissues compared with normal liver tissues. Higher expression levels of ZFPM2-AS1 were significantly associated with a less favorable prognosis of HCC, whereas higher expression levels of the ZFPM2 gene were associated with a more favorable prognosis of HCC. Genetic alterations in the ZFPM2 gene may contribute to a worse prognosis of HCC. Validation of the GSE14520 dataset also demon stared that ZFPM2 gene expression levels were significantly decreased in HCC tissues (P<0.001). The receiver operating characteristic (ROC) analysis of the ZFPM2 gene indicated high accuracy of this gene in distinguishing between HCC tissues and non-tumor tissues. The areas under the ROC curves were >0.8. Using integrated strategies, the present study demonstrated that lncRNA ZFPM2-AS1 and the ZFPM2 gene may contribute to the occurrence and prognosis of HCC. These findings may provide a novel understanding of the molecular mechanisms underlying the occurrence and prognosis of HCC.